1998
DOI: 10.1523/jneurosci.18-19-07768.1998
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neurogenesis in the Dentate Gyrus After Transient Global Ischemia in Gerbils

Abstract: Neurogenesis in the dentate gyrus of adult rodents is regulated by NMDA receptors, adrenal steroids, environmental stimuli, and seizures. To determine whether ischemia affects neurogenesis, newly divided cells in the dentate gyrus were examined after transient global ischemia in adult gerbils. 5-Bromo-2'-deoxyuridine-5'-monophosphate (BrdU) immunohistochemistry demonstrated a 12-fold increase in cell birth in the dentate subgranular zone 1-2 weeks after 10 min bilateral common carotid artery occlusions. Two mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
635
1
15

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 965 publications
(695 citation statements)
references
References 55 publications
43
635
1
15
Order By: Relevance
“…In contrast, at 90 DAI, BrdU was found in some of the CA1 neurons, supporting that these neurons indeed were formed subsequent to the ischemic injury ( Figure 2B). In agreement with previous studies (Choi et al, 2003;Liu et al, 1998;Sharp et al, 2002), the dentate gyrus showed BrdU-positive neurons at both 14 and 90 DAI (Figures 2C and 2D). In non-ischemic animals, we observed BrdU incorporation in the dentate gyrus, but not in CA1 neurons (not shown).…”
Section: Ischemia Induces Neurogenesis In the Ca1supporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, at 90 DAI, BrdU was found in some of the CA1 neurons, supporting that these neurons indeed were formed subsequent to the ischemic injury ( Figure 2B). In agreement with previous studies (Choi et al, 2003;Liu et al, 1998;Sharp et al, 2002), the dentate gyrus showed BrdU-positive neurons at both 14 and 90 DAI (Figures 2C and 2D). In non-ischemic animals, we observed BrdU incorporation in the dentate gyrus, but not in CA1 neurons (not shown).…”
Section: Ischemia Induces Neurogenesis In the Ca1supporting
confidence: 93%
“…Ischemia is a powerful stimulus to enhance cell proliferation in the subgranular zone, leading to an increase of newborn granule cells in the dentate gyrus (Choi et al, 2003;Liu et al, 1998), although the enhancement is independent of the ischemic injury (Arvidsson et al, 2001;Liu et al, 1998). Ischemia also increases generation of neurons in the subventricular zone.…”
Section: Introductionmentioning
confidence: 99%
“…In the DG, cellular proliferation was unchanged after cerebral ischemia or administration of the different treatments. It seems that cellular proliferation in the DG is not dependent on ischemic hippocampal damage (Liu et al, 1998); nevertheless, published studies after focal cerebral ischemia described divergent results Arvidsson et al, 2001). Indeed, after focal cerebral ischemia in which hippocampus was not lesioned, Zhang et al (2001) showed that the number of BrdU-immunoreactive cells in the DG was unchanged, whereas Arvidsson et al (2001) observed an increase of cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A second approach using electrophysiology to measure from GFP-retrovirally labeled cells showed that integrated neurons exhibited neuronal morphology and displayed passive membrane properties and action potentials (Song et al, 2002;van Praag et al, 2002). Furthermore, neurogenesis in the hippocampus can be induced by exogenous factors, including peripheral administration of insulin-like growth factor-I (IGF-I) (Aberg et al, 2000) or hormones like corticosteroids (Tanapat et al, 1999;Gass et al, 2000), enriched environment (Kempermann et al, 1997;Nilsson et al, 1999), exercise (van Praag et al, 1999a,b;Gould et al, 2000), or interestingly, by hypoxia (Liu et al, 1998). Unfortunately, none of these reports has demonstrated that these signals can be used as strategies for regeneration in humans.…”
Section: Physiological Function and Regulation Of Cns Stem Cellsmentioning
confidence: 99%